The effect of conservation defects on the suede quality of double-face - (:unkn) unknown (AMER LEATHER CHEMISTS ASSN, 2004)
In this research, the effects of microorganisms on suede quality of double-face leather were examined. The bacterial numbers on salted sheepskin samples were found as 1.8x10(6)-4.3x10(7) cfu/g on solid medium and 1.9x10(6)-4.7x10(7) cfu/g on halophile medium containing 10-30% NaCl. However it was found that salted sheepskins contained 4.4x10(1)-2.0x10(4) cfu/g Of fungi. While 53-74% of halophilic bacteria and 39-58% of fungi showed proteolytic activity, 47-62% of halophilic bacteria and 35-54% of fungi showed lipolytic activity. It was observed that defective light stained areas on suede surface of finished double-face leathers were caused by microorganisms on salted sheepskins and that these defects correspond to 35% of the total double-face leathers amount. Consequently, it was decided that the proteolytic and lipolytic activities of microorganisms on the flesh side of the sheepskins decreased the suede quality and caused economical losses.
Keywords: CURED CATTLE HIDES; HALOPHILIC MICROORGANISMS; DEAD-SEA; LEATHER; DIVERSITY; FUNGI; ENVIRONMENTS; PROTEASE; DESERT